1988
DOI: 10.2466/pms.1988.66.3.875
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects of Running Loss on Consistent Runners

Abstract: This study examined the psychological effects of running loss upon consistent runners. We compared a group of 30 "Prevented Runners" who were unable to run for at least two weeks with a group of 30 "Continuing Runners" who ran without interruption on the Profile of Mood States (POMS), Rosenberg Self-esteem Scale, Zung Depression Scale, and a Running Information questionnaire. We found that Prevented Runners displayed significantly greater symptoms of psychological distress, including depression, anxiety, confu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 17 publications
7
80
2
2
Order By: Relevance
“…The current findings support the notion that long-distance runners who experience a disruption in training due to an injury experience significant psychosocial distress [2] but also provide evidence of variations in psychosocial distress throughout the injury and rehabilitation process. The results of the current study add to the existing literature by indicating that a specific chronology of phases occurs during a microtrauma running injury, each with unique cognitive, affective, and behavioral responses.…”
Section: Injury Storysupporting
confidence: 75%
See 1 more Smart Citation
“…The current findings support the notion that long-distance runners who experience a disruption in training due to an injury experience significant psychosocial distress [2] but also provide evidence of variations in psychosocial distress throughout the injury and rehabilitation process. The results of the current study add to the existing literature by indicating that a specific chronology of phases occurs during a microtrauma running injury, each with unique cognitive, affective, and behavioral responses.…”
Section: Injury Storysupporting
confidence: 75%
“…Researchers have found that 79% of long-distance runners will experience an injury during one year of training [1]. Long-distance runners who experienced a disruption in training due to a sport injury reported a variety of psychosocial symptoms such as depression and anxiety as well as endorsed low self-esteem and feelings of confusion and frustration [2]. Psychosocial refers to thoughts, feelings, and behaviors experienced by injured runners, as well as the social context in which these responses occur.…”
Section: Introductionmentioning
confidence: 99%
“…Richmond et al 7 found that 18% of patients displayed major depression, depression not otherwise specified, or dysthymia a year after a minor injury. Additional authors 1,5,8,9 have reported increased incidences of depression and emotional disturbances after both chronic and serious injuries. These findings appear to be consistent regardless of whether the injury is musculoskeletal or concussion related.…”
mentioning
confidence: 99%
“…Araştırmalar evlilik, boşanma, iş değişikliği gibi yaşamlardaki stresli değişikliklerin depresyon gibi psikolojik rahatsızlıklara neden olduğunu ve spor yaralanma riskini arttırdığını; stresli yaşam değişiklikleri nedenli yaralanmaların FTİ ve FTİM sporlarda değişkenlik gösterebileceğini belirtmektedir (32 Çalışmada aktivite türlerine göre antrenman ve müsabaka sırasında meydana gelen yaralanmalarda, depresyon skorlarının klinik düzeye erişmese de FTİ sporlarda FTİM sporlara oranla istatistiksel olarak daha yüksek olduğu belirlendi. Bazı araştırmacılar, sporcuların yaralanma sonrası depresif semptomlarını hızlandıran nedenlerin yaralanmandan daha ziyade, spordan uzak kalmaya bağlı sportif rekabette geri düşme kaygısı yaşamalarından kaynaklanabileceğini savunmaktadırlar (38). Çoğunluğu takım sporu olan FTİ sporlarda yaralanmanın yanı sıra takımdan uzak kalmaya bağlı sportif rekabette geri düşme kaygısı ortaya çıkabilir.…”
Section: Discussionunclassified